2021
DOI: 10.1097/j.jcrs.0000000000000310
|View full text |Cite
|
Sign up to set email alerts
|

Scleral fixation of a 4-eyelet foldable intraocular lens in patients with aphakia using a 4-flanged technique

Abstract: A 29-gauge model test fine needle is used to create a beveled intrascleral tunnel; with microforceps, a 6-0 polypropylene suture is placed in the bore of the needle, which is used as a guide to pass and externalize the monofilament through the sclera. This maneuver is repeated by passing the suture ends through the intraocular lens (IOL) eyelets. The folded IOL is inserted and centered, the sutures are cut, and the flanges are created by thermocautery and inserted into the scleral tunnel. This technique was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 14 publications
0
40
0
Order By: Relevance
“…There were a few complications reported related to flanges such as conjunctival erosion [ 15 ] and endophthalmitis [ 16 ]. To avoid these complications, we created extra sclera tunnels to introduce the polypropylene suture away from the limbus where Tenon's capsule was thick enough to cover flanges which is described in the Surgical Technique section.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…There were a few complications reported related to flanges such as conjunctival erosion [ 15 ] and endophthalmitis [ 16 ]. To avoid these complications, we created extra sclera tunnels to introduce the polypropylene suture away from the limbus where Tenon's capsule was thick enough to cover flanges which is described in the Surgical Technique section.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The IOL is moved to the anterior chamber, cut into two pieces, and brought out through the 2.8-mm temporal clear corneal incision. A hydrophobic IOL equipped with two haptic plates forming four holes for suturing is fixated by the technique previously described by Canabrava et al, 10 with some modification. A 26-gauge needle is inserted 2 mm posterior to the limbus and the 5–0 polypropylene monofilament (Ethicon Inc, Somerville, NJ) is inserted through the corneal incision and placed into the lumen of the 26-gauge needle.…”
Section: Surgical Techniquementioning
confidence: 99%
“…Now, Canabrava et al have introduced a four-flanged intrascleral IOL fixation technique with 5–0 polypropylene that does not require flap creation, suture knots, or glue. 10 They created four fixation points by melting the tip of the suture, thereby creating flanges over the sclera. This innovative four-flange technique provides outstanding stability and centration of the fixated IOL without using suture knots.…”
Section: Introductionmentioning
confidence: 99%
“…2 Finally, Canabrava et al developed the four flanged IOL for scleral IOL fixation in aphakic patients applying a 6-0 polypropylene suture and a 29-gauge needle. 3 Mahler et al presented a modified technique for the same IOL type, the Akreos AO60 (Bausch & Lomb, Inc.), engaging a 6-0 polypropylene suture and a 30 gauge needle. 4 Moreover, Mahler et al showed a scleral fixation technique for subluxated 1-piece IOLs using a 6-0 polypropylene suture and a 30-gauge needle.…”
mentioning
confidence: 99%